Appropriating Shakespeare - Geddes, Louise (Fairleigh Dickinson University Press, 2017)
Introduction:
Includes bibliographical references and index
Keywords: Shakespeare; William; Midsummer night's dream; Pyramus (Legendary character) in literature; Thisbe (Legendary character) in literature